2021
DOI: 10.47626/1679-4435-2020-722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 testing among health workers providing care for suspected and confirmed cases

Abstract: Objectives To describe the prevalence of testing among health workers providing care for suspected and confirmed cases of COVID-19. Methods This quantitative, cross-sectional study was conducted from April to June 2020, using a convenience sample. An online questionnaire was used for collecting sociodemographic, occupational, and clinical data, which were analyzed descriptively. Results In total, 437 health workers participated in the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…In their research, Gallasch et al emphasized the need to test healthcare workers with or without minimal symptoms of SARS-CoV-2 infection. [15] For most health workers, working hours remained the same as before the pandemic or increased (Fig. 16).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In their research, Gallasch et al emphasized the need to test healthcare workers with or without minimal symptoms of SARS-CoV-2 infection. [15] For most health workers, working hours remained the same as before the pandemic or increased (Fig. 16).…”
Section: Discussionmentioning
confidence: 95%
“…Significant differences exist in the availability of healthcare workers SARS-CoV-2 testing between countries, and existing programs focus on screening symptomatic rather than asymptomatic staff. In their research, Gallasch et al emphasized the need to test healthcare workers with or without minimal symptoms of SARS-CoV-2 infection [15] . For most health workers, working hours remained the same as before the pandemic or increased (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Testing of health professionals in pandemic situations is an important tool for health care maintenance, as it provides early symptomatic treatment, enabling a shorter return to work, reducing absenteeism ( 23 ) . In this sense, the Brazilian Ministry of Health recommended that health services implement non-punitive policies, allowing professionals with respiratory infection symptoms to be distanced from work to undergo home isolation ( 21 ) , a measure that was adopted by the institutions that participated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Problems in screening and performing tests among patients and professionals were also verified in a research study that sought to analyze the work environment of nurses from Brazilian university hospitals ( 25 ) . A study carried out at the national level between April and June 2020 identified that only 27% of the health professionals had undergone some type of testing for COVID-19 ( 23 ) . This situation probably resulted from the operational limitations related to the supply of tests, considering the global shortage of inputs during a given period of the pandemic and due to slowness in processing the analyses ( 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…El testeo de los profesionales de la salud en situaciones de pandemia es una herramienta importante para que puedan seguir brindado atención sanitaria, dado que les proporciona un tratamiento sintomático temprano y les permite retomar más rápido sus funciones, lo que reduce el ausentismo (23) . Al respecto, el Ministerio de Salud de Brasil recomendó que los servicios de salud implementen políticas no punitivas, permitiendo que el profesional con síntomas de infección respiratoria se retire del trabajo para cumplir con el aislamiento domiciliario (21) , dicha medida fue adoptada por las instituciones que participaron en esta investigación.…”
Section: Sobrecarga De Trabajounclassified